Effect of Quercetin-3-O-Sambubioside Isolated from Eucommia ulmoides Male Flowers on Spontaneous Activity and Convulsion Rate in Mice - Li, Xin; Yang, Lipeng; Liu, Shaoyang; Fei, Dongqing; Zhang, Min; Zhang, Yuxian (Planta Medica, 2014)
The purpose of this study was to evaluate the effects of quercetin-3-O-sambubioside on the neural system. Quercetin-3-O-sambubioside is a monomeric compound found in Eucommia ulmoides male flowers from which it was extracted using a system solvent method. In the experiments, spontaneous activity and convulsion rate in mice were recorded, and quercetin-3-O-sambubioside shows eminent effects similar to nikethamide on increasing spontaneous activity and stimulating the nerve center to enhance excitement. These findings are indicative of the powerful ability of quercetin-3-O-sambubioside to promote the stimulation of the nerve center.
Keywords: Eucommia ulmoides; Eucommiaceae; quercetin-3-O-sambubioside; neural excitation; excitement